Superparamagnetic wood‐polypropylene nanocomposite made using magnetic wood flour with a nanoparticle‐free surface. Issue 8 (23rd December 2022) - Ahangarkolaei, Hassan Fallah; Mashkour, Mahdi; Rasouli, Davood
Abstract: This study investigates the effect of removing magnetic nanoparticles from the outer surface of magnetic wood flour (MWF) particles as a filler phase on the microstructural, physical, and mechanical properties of the prepared MWF‐polypropylene nanocomposites. For producing MWF with a surface free of magnetic nanoparticles (called LFMWF), in contrast to the commonly produced MWF (called FFMWF), magnetic wood chips were first prepared and then milled. No significant changes were observed in the tensile and flexural strength of the composite specimens prepared with the LFMWF filler instead of the FFMWF. The samples containing the LFMWF filler showed lower water uptake and higher thickness swelling after 400 h of immersion. The coupling agent's effect on improving the mechanical properties of the specimens was more pronounced than its effect on the water uptake and thickness swelling of the specimens. The saturation magnetization of LFMWF was about 4.3 emu/g, while that of FFMWF was 0.94 emu/g. After melt compounding the MWFs with the polymer matrix, the saturation magnetization decreased; this decrease was about 9.9% higher for the FFMWF‐containing magnetic nanocomposites than for the LFMWF‐containing ones. Abstract :